2008
DOI: 10.1007/s00300-008-0434-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient sediment load on blades of Arctic Saccharina latissima can mitigate UV radiation effect on photosynthesis

Abstract: We studied the short-term impact of sediment load on the photosynthetic performance of Saccharina latissima sporophytes exposed to ultraviolet radiation (UVR). The algae were collected from diVerent sedimentinXuenced environments in Svalbard in August 2007. Initial optimum quantum yield (F v /F m ) of sediment-covered sporophytes was signiWcantly higher compared to sediment-free sporophytes. Experimental sediment coating on blade discs had a photoprotective function by screening out 92% of the weighted UV-B (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…While increased turbidity (Gordeev 2006) and ice scour are liable, at least at a decadal scale, to be damaging to macroalgae, the loss of sea ice will substantially increase the area available for the development of new meadows. Long-term increases of suspended matter in the area covered by macroalgae are liable to have a downstream influence on the diversity and productivity of other elements of the biota (Roleda et al 2008;Ronowicz et al 2011). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While increased turbidity (Gordeev 2006) and ice scour are liable, at least at a decadal scale, to be damaging to macroalgae, the loss of sea ice will substantially increase the area available for the development of new meadows. Long-term increases of suspended matter in the area covered by macroalgae are liable to have a downstream influence on the diversity and productivity of other elements of the biota (Roleda et al 2008;Ronowicz et al 2011). …”
mentioning
confidence: 99%
“…During the Arctic summer, meltwater from snow and glaciers discharges substantial quantities of mineral matter into fjord systems (Zają czkowski 2002). This sediment reduces light availability and decreases the depth of the euphotic zone; it can also cover macroalgae, thereby decreasing their photosynthetic rate and hence productivity (Roleda et al 2008). Consequently, in the short-term, the overall algal biomass of Hornsund is likely to be reduced.…”
mentioning
confidence: 99%
“…Kiipli et al 2009) and ablationderived siltation in the high Arctic (cf. Roleda et al 2008) have also been observed to coat the thallus of Saccharina latissima (Figures 3b and c, respectively).…”
Section: Introductionmentioning
confidence: 85%
“…Samples were kept in darkness for 3 min and F v /F m was measured according to Roleda et al (2008). Sediment-covered discs were freed of particles before dark incubations.…”
Section: Pam-fluorometrymentioning
confidence: 99%
See 1 more Smart Citation